Exploring the Indicators of Self-Silencing in Adolescent Romantic Relationships - Petrov, Georgi; Dimitrov, Ivan (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: This study aimed to explore the psychological, relational, and sociocultural indicators of self-silencing in adolescent romantic relationships.Methods and Materials: This qualitative research employed an exploratory-descriptive design and included 25 adolescents aged 15 to 19 from Bulgaria who had been involved in at least one romantic relationship. Participants were selected through purposive sampling and data collection continued until theoretical saturation was reached. Semi-structured in-depth interviews were conducted in private settings, recorded with consent, and transcribed verbatim. Data were analyzed thematically using NVivo software, involving open, axial, and selective coding to identify categories, subcategories, and underlying concepts. Trustworthiness was ensured through member checking, peer debriefing, and maintenance of an audit trail.Findings: Three main categories were identified: emotional inhibition, power imbalance and control, and relational expectations and social norms. Subcategories under emotional inhibition included fear of rejection, shame, internalized gender norms, low emotional literacy, and discomfort with intimacy. Power imbalance and control were reflected in dominant partner behavior, fear of escalation, and emotional dependency. Relational expectations and social norms encompassed idealized views of relationships, peer influence, and cultural values promoting harmony and silence. Participants frequently described self-silencing as a strategy to maintain relationships, avoid conflict, or protect their emotional vulnerability. Gendered expectations, lack of emotional skills, and fear of judgment emerged as central factors.Conclusion: Self-silencing in adolescent romantic relationships is a multifaceted phenomenon shaped by emotional vulnerability, relational dynamics, and cultural expectations.